STRATEGI PENGEMBANGAN KAPASITAS KEPEMIMPINAN DALAM MEWUJUDKAN PENINGKATAN KINERJA PENGELOLAH JABATAN PADA BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI TENGGARA - La Selo; La Ode Muhammad Elwan; Abdul Rizal (Universitas Halu Oleo, 2018)
This study aims to explore the development of leadership capacity and empowerment of staff and to know the factors of leverage in the management of position mutations. This research was conducted in 2014. Analysis of the data used in this study was comparative analysis and SWOT analysis. The results of the research are (1) providing broad opportunities to participate in both relevant and accredited education to support the management of position mutations (2) Encouraging employees to take part in Leadership Training especially for structural office holders (3) Encouraging Civil Servants to participate in tiered Functional Training for functional officeholders, (4) Encouraging Civil Servants to participate in Technical Training for staff and officeholders in order to strengthen the implementation of tasks, (5) Encouraging Civil Servants to attend short courses, (6) developing in-house training in the context of mastering assignments for staff. The policy strategy that can be carried out is to improve the quality of the apparatus resources through formal education of SI, S2, S3 and leadership training and tennis training, improve solid policy matching in the field of apparatus development and improve the facilities and infrastructure of personnel management information systems.